Effect of Myofascial Release with Kinesiotaping on Flexibility, Strength, and Sprint Performance in Recreational Football Players with Hamstring Tightness: A Randomized Trial (International Journal of Physiotherapy, 2025)
Background: Hamstring injuries are common among recreational football players, affecting their performance and potentially requiring expensive rehabilitation. Myofascial release and kinesiotaping are known to decrease tightness and enhance muscle flexibility and function. This study examines the effect of combining Myofascial Release (MFR) with kinesiotaping versus MFR alone, evaluating the impacts on hamstring flexibility, strength, and sprint performance in recreational football players.Methods: Thirty-six participants were randomly assigned to MFR with kinesiotaping or MFR alone (18 each group) for 6 6-week program. Pre- and post-tests measured active knee extension for flexibility and strength using a modified sphygmomanometer, as well as 20m sprint performance.Results: Statistical analysis revealed significant improvements in AKE test scores, hamstring strength, and sprint times for both groups (p < 0.001). The experimental group demonstrated superior performance in AKE scores (p = 0.026) and hamstring strength (p = 0.002) compared to the control group; however, sprint improvements were comparable (p= 0.001).Conclusion: Combining MFR with kinesiotaping enhances hamstring flexibility and strength more effectively than MFR alone, in enhancing hamstring flexibility and strength among recreational football players.